Total Synthesis of the Ribosomally Synthesized Linear Azole‐Containing Peptide Plantazolicin A from Bacillus amyloliquefaciens1. Issue 36 (11th June 2013) - Banala, Srinivas; Ensle, Paul; Süssmuth, Roderich D.
<x xml:space="preserve">Abstract</x> A cyclodehydration reaction has been used to synthesize the linear azole‐containing peptide plantazolicin A. The target compound was synthesized from two heterocyclic fragments derived from dipeptide building blocks. The acid‐labile oxazolines and thiazoles necessitate the use of a Teoc/TMSE‐based protection‐group strategy, which allows structure modification of plantazolicin.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>